Breaking the Digital Barrier: Reimagining Accounting Information Systems for Micro, Small, and Medium Enterprises - I Made Dwi Hita Darmawan; Ida Bagus Ardhi Putra; Ni Putu Noviyanti Kusuma; Putu Angga Widiarta; Desak Ayu Cinta Dwiapsari (Jurnal Ilmiah Akuntansi dan Bisnis, 2026)
This study examines the barriers to the adoption of Accounting Information Systems (AIS) among micro, small, and medium enterprises (MSMEs) in Bali, Indonesia, a setting that reflects many of the institutional, technological, and resource constraints commonly faced by businesses in emerging economies. The study seeks to develop an adaptive framework for AIS implementation that is sensitive to the limited digital capabilities, managerial capacity, and financial resources of MSMEs. Employing a qualitative exploratory case study design, the study draws on in-depth interviews with 19 MSME owners and managers. The interview data were analysed using thematic analysis to identify recurring patterns, challenges, and contextual conditions influencing AIS adoption. The findings reveal six interrelated barriers: resource constraints, limited managerial competence, perceived technological complexity, resistance to change, external pressures, and fragmented integration with cloud-based solutions. These barriers do not operate in isolation; rather, they collectively shape how MSME actors perceive the usefulness, feasibility, and long-term value of AIS implementatio n.The study concludes that AIS adoption in MSMEs should be understood as a contextual and gradual process rather than a uniform technological intervention. Successful implementation requires more than access to accounting software; it depends on targeted digital literacy support, managerial capacity-building, and modular AIS designs that are affordable, user-friendly, and compatible with existing business practices. These findings offer practical implications for policymakers, technology providers, and business support institutions seeking to improve MSME financial reporting, internal control, and decision-making through more inclusive and contextually realistic AIS strategies.